If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.5X + 1.5 = 2X + -1.5 Reorder the terms: 1.5 + 2.5X = 2X + -1.5 Reorder the terms: 1.5 + 2.5X = -1.5 + 2X Solving 1.5 + 2.5X = -1.5 + 2X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-2X' to each side of the equation. 1.5 + 2.5X + -2X = -1.5 + 2X + -2X Combine like terms: 2.5X + -2X = 0.5X 1.5 + 0.5X = -1.5 + 2X + -2X Combine like terms: 2X + -2X = 0 1.5 + 0.5X = -1.5 + 0 1.5 + 0.5X = -1.5 Add '-1.5' to each side of the equation. 1.5 + -1.5 + 0.5X = -1.5 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + 0.5X = -1.5 + -1.5 0.5X = -1.5 + -1.5 Combine like terms: -1.5 + -1.5 = -3 0.5X = -3 Divide each side by '0.5'. X = -6 Simplifying X = -6
| (e^7x)=0 | | 44x+2=90 | | 16x-1=90 | | .16x^2-2.8x+1.3=0 | | 28x+3=90 | | 3(3a+2b)=3 | | 7x-3=5(x+1) | | 3x-11=5+2(x+2) | | 4(x+2)+4=-2(x-4) | | 4x^4-48x^2+128=0 | | 0.25(16+4y)-0.5(6+2Y)= | | UmgA=5x+20 | | 54.3x^2-4x^2= | | 7(x-4)8x=12+14 | | 3x+217=12x-8 | | 7(x-4)8x=26 | | 1.3*4.8= | | 5ab(a+2b)= | | z^2+(1+i)z+5+2i=0 | | (2x^2-3x-8)-(x^2-5x+10)= | | a^2(a-1)= | | 3n+3=6n+8 | | 3-6=24 | | y=-0.15x+19 | | 5p-3=-28 | | 5p-3=-29 | | g(x)=5x^2-4 | | lgx=0.5 | | 11+x=61 | | (x-5)(x-5)(x-5)=8 | | 9n-7=5n+n+27 | | (x-5)3=8 |